Business and investment opportunities in Myanmar - Wang, Jee Hee (2014)
Myanmar, breaking free from the shackles of socialist dogmas, is riding en the crest of a mini-building boom as the economy gets initiated in the ways of capitalism. Now that it has adopted an "Open Door" policy, investors from China, Singapore, Thailand, Japan and many others are flocking to the country with enormous sums of money and valuable technology. This report seeks to provide information for Singapore entrepreneurs planning to invest in Myanmar.